Reverse logistics models for the collection of Waste Electrical and Electronic Equipment: The Brazilian case - Dieste, Marcos (2019)
In 2010, the legislation regarding the Brazilian Policy of Solid Waste (BPSW) was introduced in Brazil. It is the legal framework for solid waste management that differentiates what is recyclable and from what is not. The BPSW features innovations such as Reverse Logistics (RL) which determines that manufacturers, importers, distributors and retailers must perform the collection of used packaging and products like batteries, light bulbs, electronics, etc. The aim of this paper is to propose a framework that helps indicating which would be, among the National Collective and Clearing House models used in European countries, the most suitable scheme for reverse logistics of Waste Electrical and Electronic Equipment (WEEE) according to the Brazilian reality. For this purpose, the paper analyses the existing literature and various relevant practices used in Europe. Moreover, data regarding the Brazilian environmental legislation and the characteristics of each state were used to evaluate the possible use of the European reverse logistics models. The framework helps to define the Brazilian case in three stages and suggests that the most suitable model for Brazil is the National Collective. This decision is urgent since it has been proposed that many European countries should also implement this model instead of the currently employed. Finally, a structured framework is proposed, facilitating the decision-making process to be carried out by various stakeholders such as the Brazilian Federal Government, municipal authorities, industries, recyclers and service providers. In this way, the WEEE management and logistics organization would be easier in the Brazilian territory.